2018
DOI: 10.1016/j.cub.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and circadian rhythms regulate the buoyancy of marimo lake balls

Abstract: Marimo are unusual, attractive and endangered spherical aggregations of the filamentous green macroalga Aegagropila linnaei (Figure 1A-E) [1]. Globally rare, marimo populations persist in cold freshwater lakes in Japan, Iceland and Ukraine. Marimo occupy both the lake bed and rise to the lake surface [2,3]. Here, we show that marimo buoyancy is conferred by bubbles arising from photosynthesis. We find that light-induced acquisition of buoyancy by marimo is circadian-regulated. We identify that there are circad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…And -quelle surprise?! -that is in fact what Cano-Ramirez et al [1] found: the algal balls rise to the surface of the lake [or, rather, the aquarium in their case] during the day -because of the buoyancy they get from photosynthetically-produced oxygen that is trapped in the algal 'mat' *. Understandably, one's response to this discovery might -with some justification -be to say: So?…”
Section: Algal Research That Has Its Ups and Downs…mentioning
confidence: 69%
See 3 more Smart Citations
“…And -quelle surprise?! -that is in fact what Cano-Ramirez et al [1] found: the algal balls rise to the surface of the lake [or, rather, the aquarium in their case] during the day -because of the buoyancy they get from photosynthetically-produced oxygen that is trapped in the algal 'mat' *. Understandably, one's response to this discovery might -with some justification -be to say: So?…”
Section: Algal Research That Has Its Ups and Downs…mentioning
confidence: 69%
“…Discarded plastic [1] * is a major source of this planet's pollution ("the action or process of making land, water, air, etc., dirty and not safe or suitable to use" [2] ), and which is worldwide -whether on land or on, and in, the ocean [3; 4; 5] . Seemingly, nowhere on Earth escapes this modern menace -plastics have even been detected at the bottom of the deepest parts of the ocean [6] .…”
Section: Mosses Monitor Polystyrene Plastic Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers [16] have studied the natural characteristics of Marimo; in particular, its ability to rise and sink in water, which was found to result from generation of oxygen via photosynthesis. Bubbles are formed on the surface of, and at shallow depths within, the Marimo when they are provided with illumination: it is assumed that the filamentous nature of the alga both provides numerous nucleation sites and creates a mesh through which it is difficult for the oxygen bubbles to dissipate.…”
Section: Introductionmentioning
confidence: 99%